Electric machinery fundamentals - Chapman, Stephen J. (New York, NY : McGraw-Hill Higher Education, 2012)
Electric Machinery Fundamentals continues to be a best-selling machinery text due to its accessible, student-friendly coverage of the important topics in the field. In the fifth edition, the use of MATLAB (R) continues to be incorporated in examples and problems, where applicable.
1 Introduction to Machinery Principles 2 Transformers 3 AC Machinery Fundamentals 4 Synchronous Generators 5 Synchronous Motors 6 Induction Motors 7 DC Machinery Fundamentals 8 DC Motors and Generators 9 Single-Phase and Special-Purpose Motors Appendix A Three-Phase Circuits Appendix B Coil Pitch and Distributed Windings Appendix C Salient-Pole Theory of Synchronous Machines Appendix D Tables of Contents and Conversion Factors
Includes bibliographical references and index.
EEE
Karim International
Keywords: Electric machinery; Electrical engineering